If it's not what You are looking for type in the equation solver your own equation and let us solve it.
6520=60x+4000
We move all terms to the left:
6520-(60x+4000)=0
We get rid of parentheses
-60x-4000+6520=0
We add all the numbers together, and all the variables
-60x+2520=0
We move all terms containing x to the left, all other terms to the right
-60x=-2520
x=-2520/-60
x=+42
| t-10/1=0 | | 3x-23=(-7x)+28 | | 5(4w-20)=4(5w+25) | | 15x+20-10x=5x+50 | | -15-3r=-3r=15 | | 11.25x=7= | | 5-3(n-2)=7+2n-16 | | b+3÷5=-1 | | .25x^2-8x+64=0 | | 3x-23=-7x+28 | | k/9+25=31 | | -4x+3(-3x-3)=59 | | -5x-5=4x-13 | | 3/2y-1=3 | | h/8+38=43 | | 5-3(n-2)=7=2n-16 | | 608679=x*x | | 2x+3^-1/2=0 | | 30-6m=-6m-30 | | −1.7u+3=−3.8 | | -3(f-83)=6 | | -93×15x=6x+141 | | 2^(2x+2)+9(2)^(x)=-2 | | (2x+3^-1/2=0 | | 2=1.08^x | | 24=j/7+27 | | 8k+5-10=-20 | | 7y-1=(2y+3)-2 | | 56x+112=-168 | | 608=x*x | | p/2+4=5 | | (1+x)(2x+3)^-1/2=0 |